Quick tests for soybean seeds viability evaluation - Barros, Alberto Sérgio do Rego; Filho, Júlio Marcos (Pesquisa Agropecuaria Brasileira, 2014)
The physiological quality of soybean (Glycine max (L.) Merrill) sceds evaluated by quick tests of viability, became an important tool on the quality control program for the seed producers due its practiceness and effectiveness. Considering this point of view, this research was conducted at the Seed Laboratory and Experimental Field of the Escola Superior de Agricultura Luiz de Queiroz, of Universidade de São Paulo, SP, Brazil, with the main purpose to determine the effectiveness of some quick test for viability rating. The TZ test 1-5 and the exudate pH (phenolphatalein) with 20 and 30 minutes of imbibition were compared with standard germination and field emergence tests. From this study we can draw, the following conclusions: the TZ test 1-5 and the exudate pH -1 30 minutes of imbibition were efficient to produce information about soybean seeds viability, with restriction on the seed lot where the deterioration process has progressed due its overestimation of viability